PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT (STUDI KASUS PADA RUMAH SAKIT MEDIKA PERMATA HIJAU) - Mansur; Ika Rahma Ginting; Lintong Nababan (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
The purpose of this study was to determine the effect of the variables of reliability, responsiveness, assurance, empathy, tangibility and patient satisfaction. The research method uses a field survey. Based on the results of research and discussion previously stated, the following conclusions are obtained: Partial test results for reliability variables with a statistical value tcount> ttable (4.880 > 1.986) with a value (sig) 0,000 < 0.05, then Ho is rejected, meaning there is Significant influence between reliability variables on patient satisfaction. Partial test results for the variable responsiveness with statistic value tcount> ttable (-1.751 <1.986) with a value (sig) 0.083 > 0.05, then Ha is accepted meaning that there is no significant effect between the responsiveness variable on patient satisfaction. Partial test results for the guarantee variable with a statistic value of t> t table (1.650 < 1.986) with a value (sig) 0.102 > 0.05, then Ha is accepted meaning that there is no significant effect between the guarantee variables on patient satisfaction. Partial test results for the empathy variable with a statistic value of tcount> ttable (0.661 <1.986) with a value (sig) 0.510 > 0.05, then Ha is accepted meaning there is no significant influence between the empathy variable on patient satisfaction. Partial test results for tangible variables with a statistic value of tcount> ttable (1.477 < 1.986) with a value (sig) of 0.143 > 0.05, then Ha is accepted meaning there is no significant effect between tangible variables on patient satisfaction. Simultaneous test results with the value of Fcount> Ftable or 68.279 > 2.31 and the significance < 0.05 (0.000 < 0.05), then Ho is rejected or Ha is accepted which means that there is a significant effect simultaneously (together) of the variables reliability, responsiveness, assurance, empathy and tangibility of patient satisfaction. The magnitude of the correlation value (R) of 0.885 which means that there is a correlation or a strong relationship between reliability (X1), responsiveness (X2), guarantee (X3), Empathy (X4) and tangible (X5) on patient satisfaction. The amount of Adjusted R Square (AdjR2) is 0.773 or 77.3% which means that the independent variables can explain the change in the dependent variable by 77.3% while the remaining 22.7% is influenced by other factors not included in this study.